Dampak Dwelling Time Terhadap Kegiatan Impor Di KPPBC TMP Tanjung Perak Jawa Timur - Risnaningsih Risnaningsih; Evania Ristanti Liwu (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2022)
The purpose of the research is to directly determine the effect of dwelling time on import activities in import tax receipts at the Tanjung Perak Middle Type Customs and Excise Supervision and Service Office in East Java province. In this research, the method used is descriptive quantitative, while in determining the sample to be carried out is to use total sampling so that the sample in this research will be obtained with 5 years of observation data. The data in this study uses reports on dwelling time and import tax receipts for the 2016–2020 period. In this research, the data analysis technique used is multiple linear regression analysis. The results found in the research are that dwelling time has a significant effect on import activities on import tax receipts at KPPBC Type Madya Customs Tanjung Perak with a value of t = 7.529, meaning that the more effective dwelling time will determine the increase in import activities so as to increase the revenue side of import taxes. It can be said that time dwelling can directly have an impact on the level of fluency in carrying out trade globally, which is more specifically on imports, therefore to be able to maximize the level of import tax revenue, it can be classified into several parts, including taxes in the context of imports and import duty.